The Impact of Migration on Socio-economic Development from A Research Review and Policy Implications for Dealing with Migration in the Mekong Delta - Thuan, Phan (VNU Journal of Science: Policy and Management Studies, 2023)
Migration is an inevitable social phenomenon in the development of mankind. By means of a research review, the article analyzes the impact of migration on socio-economic development. The results show that migration has a positive impact on poverty reduction and human capital; however, migration also negatively affects the health behaviors of migrants, urban poverty, and social problems. From the findings, the article provides policy implications for dealing with migration in the Mekong Delta in the coming years. Keywords: Migration, the impact of migration, socio-ecomonic development, Mekong Delta.